Traditional Culinary of Yogyakarta as a Pillar of Tourism Sustainability: A Study at Gadri Resto, Yogyakarta - Sita, Hasna Mutia; Nugroho, Setyo Prasiyono; Septemuryanto, Syaiful Ade (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Ampat Yogyakarta, 2025)
This study aims to explore the role of Gadri Resto in supporting tourism sustainability through traditional culinary practices by utilizing local ingredients, as well as identifying the use of local ingredients for culinary sustainability in Yogyakarta. A qualitative approach with a case study method is used in this research, involving a population consisting of Gadri Resto managers, domestic and international tourists, local farmers, and relevant government stakeholders. The sample was selected using a purposive sampling technique, including five restaurant managers, ten tourists, three local farmers from Bantul and Sleman, and two government representatives from the Yogyakarta Tourism Office. Data were collected through in-depth interviews, participatory observations, and documentation. The analysis technique follows Cresswell’s (2014) thematic model, which includes data reduction, data presentation, and conclusion drawing. The research findings indicate that Gadri Resto integrates sustainability elements through the use of local ingredients such as young jackfruit and palm sugar from local farmers, the presentation of traditional dishes like gudeg keraton with cultural narratives, and community empowerment through job creation. The main challenges include dependency on seasonal ingredients, fluctuations in raw material prices, and low consumer awareness regarding sustainability.